Mainstreaming Gender in Road Transport : Operational Guidance for World Bank Staff - World Bank (Washington, DC, 2014)
The paper aims to provide guidance for both transport and gender specialists on how to mainstream gender-related considerations into road transport projects to improve development effectiveness, sustainability and to reduce gender inequality. The paper draws attention to the most basic ways in which gender affects and is affected by transport policies and projects and provides practical approaches to address gender-related problems in road transport projects. Women and men have different travel and transport needs due to their different social and economic roles and activities. Women also face different constraints than men in accessing, using and paying for transport services. Transport can play a significant role in ameliorating or exacerbating the life conditions of women, particularly when poor and living in developing countries, depending on the extent to which gender differences are taken into account. The paper provides examples of entry points for mainstreaming gender into various road project contexts in urban, rural areas, highlighting documented good practices in this area. The paper identifies opportunities where women can play a role in the planning and implementation of road transport operations, particularly through participatory approaches and labor-based road construction. Included is an innovative table that presents examples of data and indicators to be collected for creating a baseline and for measuring results at the project level.